Integrating Cultural Awareness in English Language Teaching Materials - Nurdiana Nurdiana (Universitas Bunda Mulia, 2017)
Over the past few years, English has increased itself as a lingua franca of international community. Due to this fact, various problems have arisen in English Teaching. They regard to several aspects of English, e.g. grammar or vocabulary. In this paper, I shall discuss the importance of Integrating Cultural Awareness in English Teaching Materials, which I think is one of the most complex problems in teaching English as an international language.To me, culture is inseparable with language. For instance, when my students and I are discussing houses, we also talk about cultural differences regarding houses and the furniture. Americans, for example, do not use a “gayung” when they take a bath. I explain the cultural differences and tell the students that not all words in Indonesian can be translated into English because of the cultural differences. Also, the meaning of rooms designed in an American’s house is different. In Indonesia, the meaning of living room could be “ruang keluarga” whereas it is actually “ruang santai